Systemic adverse events and all-cause mortality following same-session bilateral intravitreal anti-VEGF injections: a systematic review - Bjerager, Jakob; Hajari, Javad; Klefter, Oliver Niels; Subhi, Yousif; Schneider, Miklos (Graefe's archive for clinical and experimental ophthalmology, 2024)
Purpose To review the risk of systemic adverse events and all-cause mortality following same-day bilateral anti-VEGF injections. Methods Twelve literature databases were searched for studies on same-session bilateral intravitreal anti-VEGF injections. Studies reporting on systemic adverse events and mortality were included. Data extraction was made independently by two authors and discussed afterwards until consensus was reached. Results Seven studies were included with a total of 13,406 intravitreal anti-VEGF injections (6703 bilateral injections sessions) given to 689 patients. Across all studies, mean age of patients ranged from 55.7 to 82.5 years, and mean follow-up times ranged from 1.3 to 41 months. Six studies reported on systemic adverse events: Two cases of non-fatal cardiac adverse events were reported after 12,964 injections (6482 bilateral injection sessions) in 626 patients. Four studies reported on death: 12 deaths were recorded after 6233 bilateral injection sessions in a total population of 554 subjects. Conclusions We suggest that the risk of non-fatal systemic adverse events and death after same-session bilateral anti-VEGF injection is reasonably low, but larger studies with follow-ups of several years are needed to quantify the exact risk. Study registration. Prospectively registered in PROSPERO, registration ID: CRD42023428254, registration date: 20/05/2023.